1993
DOI: 10.1083/jcb.120.4.935
|View full text |Cite
|
Sign up to set email alerts
|

Observation and quantification of individual microtubule behavior in vivo: microtubule dynamics are cell-type specific.

Abstract: Abstract. Recent experiments have demonstrated that the behavior of the interphase microtubule array is cell-type specific: microtubules in epithelial cells are less dynamic than microtubules in fibroblasts Wadsworth and McGrail, 1990). To determine which parameters of microtubule dynamic instability behavior are responsible for this difference, we have examined the behavior of individual microtubules in both cell types after injection with rhodamine-labeled tubulin subunits. Individual microtubules in both ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
162
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(183 citation statements)
references
References 24 publications
19
162
2
Order By: Relevance
“…At or near steady state, microtubules in vitro and in cells spend a considerable fraction of time in an attenuated or pause phase (19,20,22,33). LY290181 significantly increased the percentage of time that the microtubules spent in the attenuated state (Table I).…”
Section: B and C)mentioning
confidence: 98%
“…At or near steady state, microtubules in vitro and in cells spend a considerable fraction of time in an attenuated or pause phase (19,20,22,33). LY290181 significantly increased the percentage of time that the microtubules spent in the attenuated state (Table I).…”
Section: B and C)mentioning
confidence: 98%
“…Microtubules grow and shrink in cycles that yield a turnover rate of 3-5 minutes (Shelden and Wadsworth, 1993) at the population level. Conceptually, this dynamic instability offers a powerful mechanism to translate long-range directional cues on a time scale of several minutes, whereas the actin machinery turns over on a faster time scale (~30-120 seconds), which is necessary to implement an efficient protrusion -adhesioncontraction cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations have demonstrated that dynamic instability is the major pathway of microtubule turnover in living cells [Cassimeris et al, 1988;Sammak and Borisy, 1988;Schulze and Kirschner, 1988;Sheldon and Wadsworth, 1993;Tanaka and Kirschner;19911. For a variety of different cells, direct observation of either fluorescently labeled tubulin subunits or endogenous microtubules has shown that during interphase elongation typically proceeds at rates of 4-7 p d m i n [Schulze and Kirschner, 1988;Sammak and Borisy, 1988;Cassimeris et al, 1988;Tanaka and Kirschner, 19911 although rates up to -20 pni/min have been observed [Sheldon and Wadsworth, 19931.…”
Section: Dynamic Instability In Vlvomentioning
confidence: 99%
“…It is also possible that the variations in the measured elongation rates result from different experimental protocols, particularly image acquisition intervals [see Sheldon and Wadsworth, 19931. Rapid shortening occurs at rates of 10-20 p d m i n [Sammak and Borisy, 1988;Cassimeris et al, 1988;Sheldon and Wadsworth, 1993;Tanaka and Kirschner, 19911. Typically these dynamic microtubules transit between elongation and rapid shortening phases approximately 1-3 times per min [Cassimeris et al, 1988;Sheldon and Wadsworth, 1993;Tanaka and Kirschner, 19911. While dynamic instability originally described two states (elongation and rapid shortening), a third state may also exist where no detectable elongation or rapid shortening is observed.…”
Section: Equation L) Variations In Tubulin Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation